The production of subjectivity in the nurse's training - Vieira, Alcivan Nunes; Silveira, Lia Carneiro; Gomes, Antonio Marcos Tosoli (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to identify the devices for subjectivity production in the nurse's training, within the undergraduate course of Nursing in Universidade do Estado do Rio Grande do Norte (UERN). Methodology: this is a descriptive study with a qualitative approach. The research subjects were the professors and students of the Nursing School of UERN. The inclusion criteria were: being a nurse and professor of the Nursing School of UERN. The exclusion criterion was being institutionally away from teaching duties. The data were produced from the course's pedagogical project and through semi-structured interviews. The research project was approved by the Research Ethics Committee of Universidade Estadual do Ceara, under the Opinion 09553053-3. Results: it was found that there's a subjectivity production going on, which is generated through established devices: the pedagogical project and the pedagogical practices. There's also the inclusion into the health services. Conclusion: subjectivity is produced in the academic daily life, through the devices which constitute it: the course's pedagogical project and the professor-student relationship. Descriptors: nursing education; nursing professors; nursing theory. RESUMO Objetivo: identificar os dispositivos de produção da subjetividade na formação do enfermeiro, no âmbito do curso de graduação em Enfermagem da Universidade do Estado do Rio Grande do Norte (UERN). Metodologia: trata-se de estudo descritivo com abordagem qualitativa. Os sujeitos da pesquisa foram os docentes e os discentes da Faculdade de Enfermagem da UERN. Os critérios de inclusão foram: ser enfermeiro e docente da Faculdade de Enfermagem da UERN. O critério de exclusão foi estar institucionalmente afastado das atividades docentes. Os dados foram produzidos a partir do projeto pedagógico do curso e de entrevistas semiestruturadas. O projeto de pesquisa foi aprovado pelo Comitê de Ética em Pesquisa da Universidade Estadual do Ceará, com o Parecer n. 09553053-3. Resultados: identificou-se que há uma produção da subjetividade em andamento, que é gerada por dispositivos estabelecidos: o projeto pedagógico e as práticas pedagógicas. Há, ainda, a inserção nos serviços de saúde. Conclusão: a subjetividade é produzida no cotidiano acadêmico, a partir dos dispositivos que o compõem: o projeto pedagógico do curso e a relação docente-discente. Descritores: educação em enfermagem; docentes de enfermagem; teoria de enfermagem. RESUMEN Objetivo: identificar los dispositivos de producción de la subjetividad en la formación del enfermero, en el ámbito del curso de graduación en Enfermería de la Universidade do Estado do Rio Grande do Norte (UERN). Metodología: esto es un estudio descriptivo con abordaje cualitativo. Los sujetos de la investigación fueron los docentes y los discentes de la Facultad de Enfermería de la UERN. Los criterios de inclusión fueron: ser enfermero y docente de la Facultad de Enfermería de la UERN. El criterio de exclusión fue estar institucionalmente apartado de las actividades docentes. Los datos fueron producidos desde el proyecto pedagógico del curso y entrevistas semi-estructuradas. El proyecto de investigación fue aprobado por el Comité de Ética en Investigación de la Universidade Estadual do Ceará, bajo la Opinión 09553053-3. Resultados: se identificó que hay una producción de la subjetividad en andamiento, que es generada por dispositivos establecidos: el proyecto pedagógico y las prácticas pedagógicas. Hay, también, la inserción en los servicios de salud. Conclusión: la subjetividad es producida en el cotidiano académico, desde los dispositivos que lo componen: el proyecto pedagógico del curso y la relación docente-discente. Descriptores: educación en enfermería; docentes de enfermería; teoría de enfermería.